The Toponyms of Ottoman Niš: The New Barracks at Bubanj Hill - Ranđelović, Milan N. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper deals with the history and analysis of the conditions which led to the construction of one of the last barracks built in Niš by the Ottomans, only a decade and a half before they lost this city in a war against the Principality of Serbia (1878). As the New Barracks were purpose-built as a long-term solution and strategically positioned at the foot of Bubanj Hill, the paper also highlights the importance which this Ottoman military complex had as a city toponym for the development of the urban physiognomy of Niš in the decades after 1878. Various sources were used in the research, including both Serbian and Ottoman archival material, in order to draw attention to, through the example of the New Barracks, the connection between Ottoman Westernization and Serbian Europeanization of Niš, focusing on the development of its infrastructure and institutions.
Keywords: Ottoman Empire; Serbia; Bubanj Hill; Midhat Pasha; army; Niš; military barracks